Dari burnout ke burning bright: Self-care sebagai spirit kepemimpinan Kristen di era posdigital - Heryanto (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2025)
This study reexamines the urgency of integrating self-care as a foundational framework in Christian leadership within the postdigital era, where the boundaries between physical and digital spaces have become increasingly blurred, and ministry expectations are intensifying. The pressures of multitasking, constant connectivity, and the erosion of contemplative space have contributed to burnout that is not merely psychological, but structural and theological. Employing a grounded constructivist approach, this research develops a renewed theological understanding of self-care, not merely as stress management, but as a spiritual discipline that acknowledges human vulnerability as a locus of divine activity. The study formulates five pillars of a healthy leadership model to address contemporary challenges in ministry. It argues that churches will continue to reproduce fragile, exploitative, and unsustainable leadership unless there is a paradigmatic shift in leadership and a reconfiguration of structural support systems. Thus, self-care must be reclaimed as a prophetic praxis that disrupts dysfunctional ministry systems and paves the way for a resilient leadership model, rooted in grace and capable of burning bright amid an era craving authentic spiritual presence. Abstrak Penelitian ini mengeksplorasi kembali urgensi integrasi self-care sebagai kerangka fundamental dalam kepemimpinan Kristen di era posdigital, di mana batas antara ruang fisik dan digital semakin kabur, dan ekspektasi pelayanan mengalami intensifikasi. Tekanan multitugas, ekspektasi keterhubungan konstan, dan absennya ruang kontemplatif menyebabkan munculnya gejala burnout yang tidak hanya bersifat psikologis, tetapi juga struktural dan teologis. Dengan menggunakan pendekatan grounded constructivist, studi ini mengembangkan pemahaman baru tentang self-care sebagai tindakan teologis yang melampaui sekadar pengelolaan stres, melainkan sebagai disiplin spiritual yang mengakui kerapuhan manusia sebagai ruang kerja ilahi. Lima pilar model kepemimpinan sehat diformulasikan untuk menjawab tantangan kontemporer dalam pelayanan. Penelitian ini menegaskan bahwa tanpa reposisi paradigma pelayanan dan reformulasi sistem pendukung yang memadai, gereja akan terus memproduksi kepemimpinan yang rapuh, eksploitatif, dan rentan gagal. Oleh karena itu, self-care harus dilihat sebagai praksis kenabian yang membongkar struktur pelayanan disfungsional dan membuka jalan bagi model kepemimpinan yang tahan krisis, berakar pada kasih karunia, dan mampu menyala di tengah era yang haus kehadiran autentik.